PELATIHAN PUBLIC SPEAKING - Rizky, Irna Julia; D.Aksa, Yudha Asmara (LPPM Universitas Islam 45 Bekasi, 2020)
Public speaking can be understood as a technique of delivering messages in public. Scientifically, public speaking is part of the science of communication. This is because communication is a process of interaction to relate from one party to another. With this training, it is hoped that students will have the confidence to speak in public. The method used is to do public speaking training which has predetermined points. The results of this public speaking training allow students to have high self-confidence to speak in public. So that it helps students express themselves in public.